EFEKTIVITAS PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PENGAJARAN PENDIDIKAN AGAMA ISLAM MTS MIFTAHUL ULUM SUGIH WARAS - Darwanto (UNISAN JURNAL, 2024)
The use of Information and Communication Technology (ICT) has become an integral part of the educational process, including in the teaching of Islamic Religious Education (PAI) in madrasas. This research aims to investigate the effectiveness of using ICT in PAI teaching in madrasas as well as the factors that influence its implementation. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews, observations, and document analysis from PAI teachers and madrasah administration staff involved in the use of ICT. The research results show that the use of ICT in PAI teaching in madrasas has made a positive contribution to learning effectiveness. Teachers and administrative staff report that the use of multimedia and the internet allows them to present material in a more interesting and interactive manner, increasing students' interest and involvement in learning. However, there are still several factors that influence the implementation of ICT, such as inadequate technological infrastructure, limited teacher skills in mastering technology, and a lack of digital content that is in accordance with the PAI curriculum. The implications of this research include the need for increased teacher training in using ICT, investment in adequate technological infrastructure, and the development of more varied and relevant digital content. This research provides valuable insight into the role of ICT in PAI teaching in madrasas and highlights the challenges and opportunities in integrating technology in the context of Islamic religious education.